Intraoperative traction in surgery for adolescent idio- pathic scoliosis - Mikhail V. Mikhaylovskiy; Vyacheslav V. Novikov; Mikhail A. Sadovoy; Aleksandr S. Vasyura; Vasily A. Suzdalov (Хирургия позвоночника, 2017)
Objective. To analyze the effectiveness of intraoperative traction in the treatment of adolescent idiopathic scoliosis, including in relation to the initial magnitude of scoliotic curve. Material and Methods. Data on patients meeting the following criteria were selected from the electronic database and analyzed: idiopathic scoliosis (Lenke types I, III, V); age 10 to 20 years; surgery performed through posterior approach; hook or hybrid (using of pedicle screws only in the lumbar spine, at 2–4 levels) fixation; no previous history of spine surgery; and follow-up period at least two years. Results. Flattening of thoracic kyphosis and alignment of lumbar lordosis during surgical correction were significantly more pronounced in the traction group. Postoperative changes in the sagittal contour of the thoracic and lumbar spine did not differ significantly between the trac- tion and no-traction groups. Intraoperative traction was associated with significantly reduced blood loss, though operation time decreased statistically insignificantly. Normalization of the frontal imbalance in the immediate and long-term postoperative periods was different in the two groups, but these differences were insignificant. Intraoperative traction was most effective in the group with deformities of 50° to 75°, although it also increased the achieved correction in patients with scoliosis of a smaller and greater magnitude. Conclusion. The operation performed with intraoperative traction allows achieving greater correction during an intervention and smaller loss of correction during a long follow-up period than that without a distraction influence. This applies equally to both primary and sec- ondary curvatures.